Parametric Analysis of Three Layer Frequency Selective Surface for Curved Structures - Topcuoglu, Cumhur; Erbas, Cihan Dogusgen; Tokan, Nurhan Turker (IEEE, 2018)
Parametric analysis of a three layer unit cell for a designed frequency selective surface is presented. Effects of design parameters such as rectangular slot width and length, diameter of the circular patch as well as incidence angle impinging on the unit cell in terms of reflection and transmission characteristics are investigated. In future research, the designed frequency selective surface is aimed to be used for X-band curved structures such as radomes.
Keywords: curved structure; frequency selective surface; unit cell; X-band; ANTENNA; Automation & Control Systems; Computer Science; Engineering